2021
DOI: 10.1111/vox.13204
|View full text |Cite
|
Sign up to set email alerts
|

Molecular blood group screening in Omani blood donors

Abstract: Background and Objectives Blood group genotyping has been used in different populations. This study aims at evaluating the genotypes of common blood group antigens in the Omani blood donors and to assess the concordance rate with obtained phenotypes. Material and Methods Blood samples from 180 Omani donors were evaluated. Samples were typed by serological methods for the five blood group systems MNS, RH (RHD/RHCE), KEL, FY and JK. Samples were genotyped using RBC‐FluoGene vERYfy eXtend kit (inno‐train©). Predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This frameshift allele is extremely rare worldwide but has been reported in several Middle Eastern populations and is documented in the ISBT database of blood group alleles89 . Here, we found that it explained 60% of individuals with a Duffy blood group mismatch from a recent study comparing serology and targeted genotyping in Oman66 , indicating it should be incorporated in future targeted genotyping approaches for blood group inference in Oman and other AP populations. Whether it is associated with any disease phenotype in homozygotes is unknown.The high frequency of the Fy ES allele in Oman is accompanied by a striking signal of increased east African ancestry.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…This frameshift allele is extremely rare worldwide but has been reported in several Middle Eastern populations and is documented in the ISBT database of blood group alleles89 . Here, we found that it explained 60% of individuals with a Duffy blood group mismatch from a recent study comparing serology and targeted genotyping in Oman66 , indicating it should be incorporated in future targeted genotyping approaches for blood group inference in Oman and other AP populations. Whether it is associated with any disease phenotype in homozygotes is unknown.The high frequency of the Fy ES allele in Oman is accompanied by a striking signal of increased east African ancestry.…”
mentioning
confidence: 74%
“…It has also been observed before in the Middle East (frequency of 4/1002 individuals in the Greater Middle East Variome 51 ), suggesting it is more common in the Middle East than in other parts of the world. To further assess its relevance in Oman, we considered results from a previous study comparing targeted genotyping to serology in Omani individuals 66 . We identified thirteen individuals similarly predicted by genotype as expressing Fy b antigens but showing a Duffy negative phenotype by serology.…”
Section: Resultsmentioning
confidence: 99%
“…Although overall concordance was high (>95%), Fy b was an exception (concordance 87%), and only 3 antigens had 100% concordance 5 . Discordances were likely due to the effect of genetic variants that were absent from the genotyping assay.…”
Section: Introductionmentioning
confidence: 90%
“…The Duffy blood group system is a clinically remarkable blood group system 1 . It comprises six antigens (Fy a , Fy b , Fy 3 , Fy 4 , Fy 5 , Fy 6 ), and four main phenotypes; Fy(a+b+), Fy(a−b+), Fy(a+b−), and Fy(a−b−) 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…The Duffy blood group system is a clinically remarkable blood group system. 1 It comprises six antigens (Fy a , Fy b , Fy 3 , Fy 4 , Fy 5 , Fy 6 ), and four main phenotypes; Fy(a+b+), Fy(a−b+), Fy(a+b−), and Fy(a−b−). 2,3 The antigens are expressed on a glycosylated erythrocyte membrane protein known as the Duffy antigen receptor for chemokines (DARC).…”
Section: Introductionmentioning
confidence: 99%